Take a Good, Long Look in the Mirror: Adult Education, Praxis, and the Scholarship of Engagement - Susan J. Bracken (Adult Education Research Conference, 2005)
The scholarship of engagement is seemingly congruent with adult education disciplinary values yet few adult education scholars appear to be actively shaping the discourse and practice of the scholarship of engagement. This preliminary work explores the reasons why adult education scholars may not be involved, and suggests reasons to consider more visible adult education participation.